(untitled) (Research, Society and Development, 2022)
This study aimed to analyze the scientific productions disseminated in the database of the Theses and Dissertations Catalog of the Coordination for the Improvement of Higher Education Personnel (Capes) and the electronic library of the Scientific Electronic Library Online (SciELO), in the period between 2015 and 2019, with a view to understanding the interrelationships between the theoretical-practical constructs related to literacies and the proposals for continuing teacher education in the context of basic education. This is a state-of-the-art survey, with a view to identifying and qualitatively analyzing the data from the works that constituted the researched corpus. The results showed the need for theoretical-empirical (re)significations in teaching practices and literacies in basic education, as well as the need for more studies on the theme of literacies in the continuing education of teachers, given the progressive advance of information technologies and communication that have repercussions on the multiplicity of languages ​​and on socio-communicative changes, consequently on the need to update the teaching and learning processes.